PENGARUH ONLINE CONSUMER REVIEW DAN IKLAN TEHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE TOKOPEDIA(Studi Pada Mahasiswa Jurusan Administrasi Niaga Program Studi D4 Manajemen Pemasaran Politeknik Negeri Malang) - Mashita Sekar Dewi; Asminah Rachmi (CV. ADIBA AISHA AMIRA, 2024)
The internet has changed people's lifestyles. This is an opportunity for the e-commerce company Tokopedia to create an online selling platform that functions to meet people's demands and supply. By providing the best offers, the Tokopedia company is able to compete and attract consumers' interest. This study aimed to determine the effect of online consumer reviews and advertisements on purchasing decisions on the Tokopedia marketplace. This research is quantitative. The data collection method used was distributing questionnaires to 102 respondents with the purposive sampling technique. The analysis of the research data was conducted with multiple regression analysis and hypothesis testing. Online consumer review and advertising variables partially have a positive effect on the purchasing decisions. Then the results of testing the F hypothesis (simultaneous) explained that online consumer review, and the advertising variables together have a positive effect on purchasing decisions. The online reviews feature quality and increase purchases as well as optimize the display of advertisements that are unique and of high quality in order to attract consumers' interest